2023
DOI: 10.3390/ma16010442
|View full text |Cite
|
Sign up to set email alerts
|

Study of Transition Areas in Press-Hardened Steels in a Combined Tool for Hot and Cold Forming

Abstract: Press-hardening, also known as hot stamping, is a manufacturing process for producing car body parts that must meet the high demands of their mechanical properties and safety parameters. Moreover, these components often require different mechanical properties in different parts of the component. This work presents the press-hardening process in a special combined tool where one half of the tool is heated and the other half is cooled. The cooled part has been 3D printed due to the complexity of the internal coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The lower part with lower strength and higher ductility absorbs the energy generated in a collision. The production of such tailored parts is very complex and uses various methods [ 10 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower part with lower strength and higher ductility absorbs the energy generated in a collision. The production of such tailored parts is very complex and uses various methods [ 10 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another way is to change the heating or cooling parameters during the hot-pressing process. In this case, one part of the hardening tool is heated and another part of the forming tool is cooled [ 15 , 16 , 18 ]. One other possibility is the inclusion of a device allowing local annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing concepts are aimed at something other than use in structural parts requiring high loads. This can only be achieved by appropriate hardening and tempering [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This also resulted in locally different mechanical properties and microstructures. In addition, a study by Votava et al [28] using a special die with differently tempered areas showed that controlled variation of sheet microstructure and mechanical properties can be achieved as a function of the cooling process in the die. These recent results clearly show that detailed knowledge of the local cooling rates throughout the part is necessary to realize the full potential of Q&P heat treatments in a forming process and to later predict part properties with a high degree of confidence.…”
Section: Introductionmentioning
confidence: 99%